Incorporating seismic attribute variation into the pre-well placement workflow, a case study from Ness County, Kansas, USA - Abbas, Mazin Y. (Kansas State University, 2009)
3D seismic surveys have become the backbone of many exploration programs because of their high resolution and subsequent success for wildcat test wells. There are occasions when the predicted subsurface geology does not agree with the actual geology encountered in the drilled well. A case in point occurred during the drilling of several wells based upon a 3D seismic survey in Ness County, Kansas, where the predicted Cherokee Sand did not meet the expectations. By better understanding the subsurface geologic features in the subject area, this study will attempt to answer the question “what went wrong?” Seismic attribute analysis workflow was carried out and the results were correlated to the available geological and borehole data within the survey boundaries. The objective of running this workflow was to describe facies variations within the Cherokee Sandstone. Correlations between seismic attributes and physical properties from well data were used to define these variations. Finally, Distributions of the seismic facies were mapped to predict the distribution of potential reservoir rocks within the prospect area.
Keywords: Geology; Geophysics; Seismic attributes; Geology (0372); Geophysics (0373)